Combined high-intensity interval and resistance training improves cardiorespiratory fitness more than high-intensity interval training in young women with overweight/obesity: a randomized controlled trial - Wang, Yifei; Yang, Xin; Deng, Jiamei; Wang, Zhenshan; Yang, Dongxue; Han, Yanbai; Wang, Hongli (Frontiers in Endocrinology, 2024)
Objective: This study aimed to compare the effects of high-intensity interval training (HIIT) combined with resistance training (RT) versus HIIT alone on body composition, cardiorespiratory fitness and glycolipid metabolism in young women with overweight/obesity. Methods: This randomized controlled trial divided 40 subjects into an experimental group (HIIT+RT) and a control group (HIIT). Both groups underwent training three times per week for eight weeks. Body composition, cardiorespiratory fitness and glycolipid levels were assessed before and after the intervention. Results: The results revealed that compared to baseline, both the experimental and control groups showed significant improvements in body weight, body mass index (BMI), Body fat, waist circumference (WC), waist-hip ratio (WHR), peak oxygen uptake (VO2peak), vital capacity (VC), oxygen pulse (VO2/HR), minute ventilation, resting heart rate, blood oxygen saturation, blood pressure, fasting blood glucose, triglycerides and high-density lipoprotein cholesterol (p<0.05). Additionally, a significant increase in muscle mass and a significant reduction in 2-hour postprandial glucose were observed in the experimental group (p<0.05). Muscle mass (mean difference: 2.75%), VO2peak (mean difference: 1.61 mL/min/kg), VC (mean difference: 334mL), and VO2/HR (mean difference: 0.51mL/beat) showed greater improvement in the HIIT+RT group compared to the HIIT group (p<0.05). Conclusion: In conclusion, an 8-week regimen of either combined HIIT and RT or HIIT significantly improves body composition, cardiorespiratory fitness and glycolipid metabolism in women with overweight/obesity. However, the combined training appears to offer more benefits than HIIT alone. Further research is needed to evaluate the longterm effects and feasibility of combined training. Trial registration: chictr.org.cn: identifier: ChiCTR2300075961